Database Integration Model for Automatic Identification System and Shipping Database In Real Time Traffic Monitoring - Maulidi, Akhmad; Pitana, Trika; Artana, Ketut Buda; Dinariyana, A.A. Bagus; Zaman, Muhammad Badrus; Masroeri, Agoes A.; Sembiring, Ricky Randall (Institut Teknologi Sepuluh Nopember, 2014)
In recent years, there are so many marine accidents in the world such as ship sinking (37%), grounding (13%), collisions (15%), fire (18%) and other types of accidents (17%). While the causes of the ship accident are 37% of human error, technical error of 23%, 38% due to natural conditions, and 2% to other causes. One of the causes is the weakness of the identification and monitoring the ships passing through the shipping channel in Indonesia. Automatic Identification System (AIS) on the previous research has been carried out with the integration of Geographic Information System (GIS) that allows measuring the use of AIS for fuels monitoring and the development of ship inspection priority system based on the level of risk held by each vessel. Those studies are expected to minimize the level of accidents that occurred in Indonesian waters. However, the result of previous studies showed that the identity of the ship is still conducted separately. It is thus necessary to perform data integration with databases AIS vessel into a database server. This research is focused on the development of the integration between AIS data and shipping database, therefore, It could be used as the backbone of integration system for measuring safety and pollution of the ships, such as basis for monitoring traffic analysis, estimates of air pollution, vessel inspections in real time and direct search vessel identity.